Job Retention in Call Centers Delhi India - Khan, Hisham Ali (2006)
In my project I have analyzed the reasons for high attrition rate of employees in call centers. Attrition refers to a method of achieving a reduction in personnel by not refilling positions which are vacated due to resignation, reassignment, transfer, retirement or means other than lay off. The fact that large number of employees turnover in the first six months of employment suggests that this is very critical time for helping people adjust to new roles . Managing employee’s expectations should actually start before employment. A realistic job preview would ensure that the employees walk into their jobs knowing exactly what they are supposed to and what is expected from them. The orientation program conducted should not be a one day event, they should span for the first three months of employment. A good orientation program basically helps to prevent misunderstanding and it gradually introduces the employees into the organization. It provides just in time information and training rather than one day of information. And so as a result the training efforts would yield much better results. Business Process Outsourcing sector is one of the major drivers of the Indian economy. The employee turnover is as high as 25% to 35%; it is one of the biggest challenges which the call centre faces. In order to retain the employees the call centre should adapt innovative practices. In order to retain the employees the call centers are resorting to various strategies from giving luxury comfort to its employees like housing scheme , low rate loan , pick and drop facility , attractive catering . Spouses working in the same organization, signing anti poaching agreement to retain the people. The study provides an insight about the reasons for high attrition rate in call centers in Delhi India. The study not only discusses about the problems of the employees and at the same time we also discuss about the possible practice which would reduce the exit of the employees from the organization. It provides information about the business process outsourcing industry which is fast expanding and is considered as the key driver for growth of the Indian economy.